KONSTRUKSI SOSIAL ATAS RELIGIUSITAS MASYARAKAT PEDESAAN: ANALISIS FENOMENA KEAGAMAAN DI DESA KENJO, BANYUWANGI - Eriza Lutfianto; Agus Machfud Fauzi; Khalid Syaifullah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
AbstractThis research focuses on the dynamics of religiosity in rural communities, which are formed through social interactions and daily religious practices. This phenomenon is interesting to study because religiosity is not only interpreted as a form of individual devotion but also as a result of social processes that occur in community life. The purpose of this research is to understand how the people of Kenjo Village, Glagah District, Banyuwangi, construct and interpret their religiosity through social construction. The approach used was qualitative with a constructivist paradigm. Data were collected through participant observation, in-depth interviews, and documentation of religious activities in the community. The results indicate that the religiosity of the Kenjo Village community is formed through three dialectical stages, as proposed by Berger and Luckmann: externalization, objectivation, and internalization. The externalization process is evident in religious activities such as tahlilan (religious gatherings), pengajian (religious study groups), and selamatan (celebration ceremonies), which serve as a means of expressing spiritual and social values. Objectivation occurs when these practices are accepted as social norms passed down across generations. Meanwhile, internalization occurs through family education and religious institutions, which instill religious meaning as part of the community's social identity. The conclusion of this study indicates that the religiosity of rural communities is not static, but rather is continuously formed and renewed through social and cultural interactions. These findings confirm that religion has a crucial social function in maintaining community cohesion while strengthening the construction of collective meaning in life.